Characterization of clinical outcomes after shorter course hypofractionated and standard-course radiotherapy for stage I-III curatively-treated Merkel cell carcinoma. (August 2022) - Liu, Kevin X.; Milligan, Michael G.; Schoenfeld, Jonathan D.; Tishler, Roy B.; Ng, Andrea K.; Devlin, Phillip M.; Fite, Elliott; Rabinowits, Guilherme; Hanna, Glenn J.; Silk, Ann W.; Yoon, Charles H.; Thakuria, Manisha; et al.
Highlights: Efficacy of hypofractionated radiotherapy for Stage I-III Merkel cell carcinoma is not well-described. There was no difference in cumulative incidence of in-field locoregional relapse or MCC-specific survival between hypofractionated and conventionally-fractionated radiotherapy. On multivariable analysis, immunosuppression, clinical stage III disease, and lymphovascular invasion were associated with any recurrence when controlling for sex, age, and hypo-RT. Abstract: Background: Limited data exists regarding the efficacy of curative hypofractionated radiotherapy (hypo-RT) regimens compared to conventionally-fractionated radiotherapy (conv-RT) for Merkel cell carcinoma (MCC). Methods: A retrospective analysis of 241 patients diagnosed with non-metastatic MCC from 2005-2021 and who received RT at Dana-Farber/Brigham & Women's Cancer Center. The primary outcome was cumulative incidence of in-field locoregional relapse using Gray's test with competing risks of death and isolated out-of-field recurrence. Secondary outcomes included overall survival (OS) and MCC-specific survival using log-rank tests, and risk factors of recurrence using Cox-proportional hazards regression. Results: There were 50 (20.6 %) and 193 (79.4 %) courses of hypo-RT and conv-RT, respectively. The hypo-RT cohort was older (≥73 years at diagnosis: 78.0 % vs 41.5 %, p < 0.01), and received a lower equivalent total RT dose in 2 Gy per fraction (<50 Gy: 58.0 % vs 5.2 %, p < 0.01). Median follow-up was 65.1 months (range: 1.2–194.5) for conv-RT and 25.0 months (range: 1.6–131.3) for hypo-RT cohorts. Two-year cumulative incidence of in-field locoregional relapse was low in both groups (1.1 % conv-RT vs 4.1 % hypo-RT, p = 0.114). While two-year OS was lower for the hypo-RT group (62.6 % vs 84.4 %, p = 0.0008), two-year MCC-specific survival was similar (84.7 % vs 86.6 %, p = 0.743). On multivariable analysis, immunosuppression, clinical stage III disease, and lymphovascular invasion were associated with any-recurrence when controlling for sex, age, and hypo-RT. Conclusions and Relevance: There was no difference in cumulative incidence of in-field locoregional relapse or MCC-specific survival between hypo-RT and conv-RT. Prospective studies are needed to confirm hypo-RT as an efficacious treatment option for MCC.